106k views
1 vote
Given: M ≅ X
N ≅ Y
YO ≅ NZ
Prove: △MNO ≅ △XYZ

Given: M ≅ X N ≅ Y YO ≅ NZ Prove: △MNO ≅ △XYZ-example-1
User Gsimoes
by
5.3k points

1 Answer

3 votes

Answer:

Δ MNO ≅ ΔXYZ ⇒ proved down

Explanation:

Cases of congruency

  • SSS ⇒ 3 sides in the 1st Δ ≅ 3 sides in the 2nd Δ
  • SAS ⇒ 2 sides and including angle in the 1st Δ ≅ 2 sides and including angle in the 2nd Δ
  • ASA ⇒ 2 angles and the side whose joining them in the 1st Δ ≅ 2 angles and the side whose joining them in the 2nd Δ
  • AAS ⇒ 2 angles and one side in the 1st Δ ≅ 2 angles and one side in the 2nd Δ
  • HL ⇒ hypotenuse and leg of the 1st right Δ ≅ hypotenuse and leg of the 2nd right Δ

Let us solve the question using the 4th rule above

YZ = YO + OZ

NO = NZ + ZO

∵ OZ = ZO ⇒ from the figure

∵ YO ≅ NZ ⇒ given

YZ NO

In Δs MNO and XYZ

∵ ∠M ≅ ∠X ⇒ given

∵ ∠N ≅ ∠Y ⇒ given

∵ NO ≅ YZ ⇒ proved

→ By using the AAS postulate of congruency.

Δ MNO ≅ ΔXYZ

User KVK
by
5.9k points